PENGEMBANGAN MEDIA FLIPBOOK PADA PEMBELAJARAN TEMATIK TEMA 1 SUBTEMA 1 KELAS V - Masyinta Maghfirah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The background of this developmental study was to determine the effectiveness of Flipbook learning media at MI Al-Muddatsir Kemulan Turen by using digital media for different learning themes in class V on topic 1 subtheme 1 (animal and plant locomotor organs). This development method is R&D (research and development) using ADDIE mode, there are several stages of this mode (analysis, design, development, implementation and evaluation). The software used is Flip PDF Corporation. The data collected is in the form of Flipbook Validity Data and Flipbook User Responses. The validity was measured on the basis of test data from media experts, material experts and teachers of the fifth grade, after which the collected data were converted into a Likert scale. Flipbook respondents subjects were taken from 8 students in class V (small group test) and 30 students in class V (large group test). The results of the development show (1) the validity of media experts, materials experts and teachers in the classroom is “very achievable” with an overall mean score of 93.3% (2) student responses to flipbook 78% out of 76 %-100% range with